Republic of Armenia : Country Procurement Assessment Report - World Bank (Washington, DC, 2013)
Along with assessing the comprehensiveness, transparency, and competitiveness of Armenia's public procurement system, this CPAR addressed specific issues of importance to Government. The MOFE has been advocating that procurement using extra-budgetary donor funds follow the same rules as budget-funded procurement, with the SPA playing the same role. The Authorized Body, which regulates and monitors public procurement (attached to the Ministry of Finance) has been keen to introduce electronic procurement and has already hired a firm to develop specifications. The Ministry of Defense (MOD) has established an internal procurement department and requested the CPAR team's advice in its effort to identify which of its purchases could be suitable for open bidding, as required by law. Therefore the CPAR covers these four key topics: (1) the current degree of centralization of procurement control within the State Procurement Agency; (2) gradual transfer of experience and authority for procurement using Bank funds from Project Implementation Units to the line ministries; (3) the potential for introducing electronic catalogues for periodic procurement and the strategy for introducing other e-procurement uses; and (4) introduction of open bidding procedures for the procurement of non-sensitive items by the Ministry of Defense (MOD). The CPAR presents concrete recommendations that would contribute to three of the five core fiscal strategy objectives of the PER: (1) provide for major improvements in budget accountability to ensure that incremental resources are spent in a transparent and efficient way, (2) increase expenditures on basic health and education, and (3) ensure more efficient use of budget resources. In turn, the CPAR identifies ways in which budget planning and execution, which are a major focus of the Country Financial Accountability Assessment, significantly contribute to overuse of single-source and other non-competitive procurement methods.